Political power and social theory. Vol. 14 - Davis, Diane E., 1953- (Amsterdam [Netherlands] ; London : JAI, 2001)
This volume of "Political Power and Social Theory" deliberately grapples with some of the weightiest subjects in the contemporary social sciences: race and class and their impact on political and economic organization. Three historical papers on Cuba, Tanzania, and Mexico open the volume by exploring the complex relations between race, class, ethnicity, and nationalism. Two subsequent papers, which draw on the contemporary case studies of Chile and South Africa, focus on the intersection of class, race, ethnic and generational identities in the contested appropriation of space and territory.The volume concludes with a dynamic debate structured around the question 'Whither Class?' in which the eminent sociologist Alejandro Portes makes a deliberately provocative call to arms. Portes urges a rethinking of class and proposes a new type of class analysis in light of some of the recent social, political, and economic changes of our times. He is rejoined by a distinguished interdisciplinary panel of scholars including Richard Sennett, Edna Bonacich, Richard Ratcliff, Zine Magubane and David Grusky, each of whom examine his position and offers their own view of the continuing relevance of class-based theories. With their contributions, the volume circles back to complex questions of race and other multifaceted forms of identity that increasingly capture the imagination of social scientists in the modern world.
Description based on print version record.
Keywords: Power (Social sciences); Political sociology; Social sciences -- Philosophy; Social theory; Political science & theory; Political Science -- General